Biodentine-a novel dentinal substitute for single visit apexification - Gurudutt Nayak; Mohammad Faiz Hasan (Korean Academy of Conservative Dentistry, 2014)
Use of an apical plug in management of cases with open apices has gained popularity in recent years. Biodentine, a new calcium silicate-based material has recently been introduced as a dentine substitute, whenever original dentine is damaged. This case report describes single visit apexification in a maxillary central incisor with necrotic pulp and open apex using Biodentine as an apical barrier, and a synthetic collagen material as an internal matrix. Following canal cleaning and shaping, calcium hydroxide was placed as an intracanal medicament for 1 mon. This was followed by placement of small piece of absorbable collagen membrane beyond the root apex to serve as matrix. An apical plug of Biodentine of 5 mm thickness was placed against the matrix using pre-fitted hand pluggers. The remainder of canal was back-filled with thermoplasticized gutta-percha and access cavity was restored with composite resin followed by all-ceramic crown. One year follow-up revealed restored aesthetics and function, absence of clinical signs and symptoms, resolution of periapical rarefaction, and a thin layer of calcific tissue formed apical to the Biodentine barrier. The positive clinical outcome in this case is encouraging for the use of Biodentine as an apical plug in single visit apexification procedures.